Imaging Neurotensin Receptor in Prostate Cancer With Cu-Labeled Neurotensin Analogs - Huaifu Deng MD; Hui Wang PhD; He Zhang MD; Mengzhe Wang MS; Ben Giglio PhD; Xiaofen Ma MD; Guihua Jiang MD; Hong Yuan PhD; Zhanhong Wu PhD; Zibo Li PhD (Molecular Imaging)
Introduction: Neurotensin receptor 1 (NTR-1) is expressed and activated in prostate cancer cells. In this study, we explore the NTR expression in normal mouse tissues and study the positron emission tomography (PET) imaging of NTR in prostate cancer models. Materials and Methods: Three 64 Cu chelators (1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid [DOTA], 1,4,7-triazacyclononane-N,N′,N″-triacetic acid [NOTA], or AmBaSar) were conjugated to an NT analog. Neurotensin receptor binding affinity was evaluated using cell binding assay. The imaging profile of radiolabeled probes was compared in well-established NTR + HT-29 tumor model. Stability of the probes was tested. The selected agents were further evaluated in human prostate cancer PC3 xenografts. Results: All 3 NT conjugates retained the majority of NTR binding affinity. In HT-29 tumor, all agents demonstrated prominent tumor uptake. Although comparable stability was observed, 64 Cu-NOTA-NT and 64 Cu-AmBaSar-NT demonstrated improved tumor to background contrast compared with 64 Cu-DOTA-NT. Positron emission tomography/computed tomography imaging of the NTR expression in PC-3 xenografts showed high tumor uptake of the probes, correlating with the in vitro Western blot results. Blocking experiments further confirmed receptor specificity. Conclusions: Our results demonstrated that 64 Cu-labeled neurotensin analogs are promising imaging agents for NTR-positive tumors. These agents may help us identify NTR-positive lesions and predict which patients and individual tumors are likely to respond to novel interventions targeting NTR-1.